Tratamiento Contable del Inventario de la Empresa Agro Repuestos Alvarado - Mariscal León, Alejandra Rosa (2020)
Abstract The Agrorepuestos Alvarado Company is a private company whose main activity is the wholesale of agricultural machinery and equipment, as an established company must carry out the management and execution of all its assets, which the administration must internally support in a true way. As a private company, it is not subject to the Ecuadorian legal regulations established by the government for its management, and it is not under the control of the Superintendence of Companies. Therefore, it is free to take control of the inventory in the most convenient way. The entrances - exits of the merchandise as well as its supply must be supervised by the person in charge in an effective and efficient way, having the knowledge of the inventory valuation recommended by IAS 2 Inventory, which is known as the FIFO Method (First to Enter First to exit). For the development of the following case study called “Accounting treatment of the Inventory of the Agrorepuestos Alvarado Company” the methodology applied were the techniques of observation and interview to know exactly the execution and control of the merchandise that It is available in the cellar.